(untitled) (Journal of Environmental Microbiology and Toxicology, 2017)
Sodium dodecyl sulphate (SDS) is an anionic surfactant that is mostly used in cleaning detergents and commercial products. Its toxicity and pollution in the environment are well documented. In recent years, the use of SDS-degrading bacteria for the purpose of bioremediation of this pollutant has increased several folds. The number of SDS-degrading microorganism are increasingly reported indicating the seriousness of researchers to embark on process and systems for SDS remediation. Despite these efforts, several aspects that still need to be settled are the mechanism of SDS utilization by microorganisms, kinetics of degradation and growth on SDS, the fate and toxicity of degraded and undegraded metabolites, and the potential of using these microorganisms in actual field work. These issues are going to hinder the successful development of efficient systems for SDS remediation in water bodies and soils.